PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION - Catur Widayati (Universitas Mercu Buana, 2019)
This research aims is to understand influence of leadership style, compensation and organizational commitment to employee turnover intention. There are three independent variables and one dependent variable, namely leadership style, compensation and organizational commitment as the independent variables and turnover intention as dependent variable. The object of this research is employer who works at PT NP international located in Jakarta. This research was done to 35 respondents by using quantitative descriptive approach and saturated sample technique. Thus, data analysis is conducted by using multiple linier regression and is processing by using SPSS program version 23. The results of this research shows that leadership style and organizational commitment have a negative and significance influence towards turnover intention, and compensation has a positive and significance influence towards turnover intention